Vertical distribution of sources and sinks of volatile organic compounds within a boreal forest canopy - Petersen, Ross; Holst, Thomas; Mölder, Meelis; Kljun, Natascha; Rinne, Janne (Copernicus GmbH, 2023)
The ecosystem–atmosphere flux of biogenic volatile organic compounds (BVOCs) has important impacts on tropospheric oxidative capacity and the formation of secondary organic aerosols, influencing air quality and climate. Here we present within-canopy measurements of a set of dominant BVOCs in a managed spruce- and pine-dominated boreal forest located at the ICOS (Integrated Carbon Observation System) station Norunda in Sweden, collected using proton-transfer-reaction mass spectrometry (PTR-MS) during 2014–2016 and vertical emission profiles derived from these data. Ozone concentrations were simultaneously measured in conjunction with these PTR-MS measurements. The main BVOCs investigated with the PTR-MS were isoprene, monoterpenes, methanol, acetaldehyde, and acetone. The distribution of BVOC sources and sinks in the forest canopy was explored using Lagrangian dispersion matrix methods, in particular continuous near-field theory. The forest canopy was found to contribute ca. 86 % to the total monoterpene emission in summertime, whereas the below-canopy and canopy emissions were comparable (ca. 42 % and 58 %, respectively) during the fall period. This result indicates that boreal forest litter and other below-canopy emitters are a principal source of total forest monoterpene emissions during the fall months. During night, our results for methanol, acetone, and acetaldehyde seasonally present strong sinks in the forest canopy, especially in the fall, likely due to the nighttime formation of dew on vegetation surfaces.